The political legacies of wartime resistance: How local communities in Italy keep anti-fascist sentiments alive - Simone Cremaschi; Juan Masullo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Can past wartime experiences other than violence have long-term effects on political attitudes and behaviours? How are these legacies sustained across generations and beyond those who directly experienced war? We explore these questions in Italy, a country whose democratic institutions were forged after a civil war (1943-45) fought between an armed resistance movement and Nazi-Fascist forces. We argue that local experiences of resistance left anti-fascist legacies that can be translated into contemporary political action. We detail a process of community-based intergenerational transmission linking past wartime experiences and recent political outcomes consisting of three core activities-memorialization, localization, and mobilization-put forward by memory entrepreneurs. To empirically substantiate this argument, we use a multi-method design that combines a statistical analysis of original georeferenced data across Italian municipalities and a within-case analysis of a purposely selected locality. Our study advances the growing literature on the long-term political legacies of war by improving our understanding of the processes and mechanisms underlying the transmission of political memories over time and across generations. Moreover, it emphasizes armed resistance as a critical source of war's longterm political legacies and explores political effects beyond electoral and party politics.
Keywords: H7; N4; 330; civil war; resistance; Italy; collective memories; political legacies